2001
DOI: 10.1034/j.1600-0447.2001.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of psychosocial outcome in patients with bipolar disorder

Abstract: This review highlights the fact that inter-episode functional recovery is incomplete in some patients, suggesting that comprehensive rehabilitative assessment and intervention may be essential to reduce the morbidity associated with this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
179
1
7

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(200 citation statements)
references
References 77 publications
13
179
1
7
Order By: Relevance
“…31,32 However, contradictions about which factors predict outcomes are frequent in the literature. [13][14][15]31,33 The major reason of this inconsistency and higher number of previous depressive episodes predict the occurrence of new depressive episodes and their greater intensity. Therefore, more effective BD treatments should be developed, particularly for the management of depressive episodes, as they seem to have a greater impact on outcome.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 However, contradictions about which factors predict outcomes are frequent in the literature. [13][14][15]31,33 The major reason of this inconsistency and higher number of previous depressive episodes predict the occurrence of new depressive episodes and their greater intensity. Therefore, more effective BD treatments should be developed, particularly for the management of depressive episodes, as they seem to have a greater impact on outcome.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the high number of episodes may determine brain long-lasting biochemical changes that could have some consequences on global functioning in bipolar patients (Young et al 1993, Post 1993. Moreover, some investigators have found that cognitive dysfunctions could worsen psychosocial outcome and employment in bipolar illness (Zarate, Jr. et al 2000, MacQueen et al 2001, Martinez-Aran et al 2004a. Patients with multi-episode bipolar disorder would be more prone to have cognitive impairment (Martinez-Aran et al 2004b), and this fact may be on the basis of poor social and occupational adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Data from 1450 patients showed that 30-60% of bipolar patients had detectable levels of psychosocial impairment (MacQueen et al 2001). Long duration illness has been associated with impaired social functioning (Hajek et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…3 Of course, a clear relationship exists between symptom/syndromal outcome and functional outcome. 4 This relationship, however, is far from linear and may best be described as circular, with poor outcome in either domain predicting poor outcome in the other domain.…”
Section: Natural History Of Treated Bipolar Disordermentioning
confidence: 99%